Arteriovenous Malformation of the Oral Cavity - S. M. Manjunath; Sujan Shetty; Ninad J. Moon; Bhushan Sharma; Kiran Kumar Metta; Nitin Gupta; Sandeep Goyal; Simranjit Singh (Case Reports in Dentistry)
Vascular anomalies are a heterogeneous group of congenital blood vessel disorders more typically referred to as birthmarks. Subcategorized into vascular tumors and malformations, each anomaly is characterized by specific morphology, pathophysiology, clinical behavior, and management approach. Hemangiomas are the most common vascular tumors. Lymphatic, capillary, venous, and arteriovenous malformations make up the majority of vascular malformations. Arteriovenous malformation of the head and neck is a rare vascular anomaly but when present is persistent and progressive in nature and can represent a lethal benign disease. Here we present a case report of a 25-year-old male patient with arteriovenous malformation involving the base of tongue.